Cultural Competence of Professionals Working With Unaccompanied Minors: Addressing Empathy by a Shared Narrative - Radjack, Rahmeth; Touhami, Fatima; Woestelandt, Laure; Minassian, Sevan; Mouchenik, Yoram; Lachal, Jonathan; Moro, Marie Rose (Frontiers in Psychiatry, 2020)
Background: The number of migrant minors traveling without parents continues to rise in Europe and North America. Some of them leave their home countries on their own and find themselves in a new country, separated from their family and cut off from their cultural roots. Besides those who leave to study, work, and pursue a better life, others are escaping war-torn countries. They need adequate social, educational, and therapeutic spaces, where they can feel entitled to speak. Social workers often ask about how they can understand these minors better so that they can provide them with better care (cope with their trauma and suspicion, deal with the cultural distance between the adolescents and their social workers, etc). Aim: At Cochin Hospital in Paris, we led a participative action-research program to transmit cultural competence to social workers who provide care for these minors. The aim is for these teenagers to share their representations about themselves. Methods: This study used a qualitative method that mixed narrative and transcultural approaches. Two researchers met each minor and social worker with an interpreter-cultural mediator three times (once a month) to assess changes in their relationships during the study. Minors were asked to bring 3 items of their choice, representing their past, present, and future. They could use their imagination and creativity. We also used the circle test described by Cottle for this purpose. We used a phenomenological approach to analyze the interviews. Results and discussion: This study included 29 minors from 13 different countries. A transcultural approach appears to be a useful framework for re-activating their identity construction process. It promotes the emergence of cultural representations and takes their experiences before, during, and after migration into account. We assisted them in developing their ability to produce a thorough narrative of their bicultural adolescences. Conclusion: Together, a transcultural approach and methods stimulating the production of narrative are relevant ways to help children to describe their representations of themselves, especially those who have learned to protect themselves by remaining silent. This protocol could be useful for both preventive action and therapy for psychotrauma.